2017
DOI: 10.1097/wco.0000000000000431
|View full text |Cite
|
Sign up to set email alerts
|

Depression in epilepsy

Abstract: New studies will focus on the development of shared clinical pathways between neurology and psychiatry for mood disorders and suicide prevention. New global campaigns on the double stigma will support this process in areas where psychiatric comorbidities are still underdiagnosed and undertreated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 83 publications
3
31
0
Order By: Relevance
“…To date, neurological/psychiatric comorbidities represent a severe problem in PWE. As reported, comorbidities sometimes can be more harmful than seizures themselves [32,34]. The "face validity" of this animal model was also supported by the potential antiepileptogenic effect of ETH both in childhood absence epilepsy and this strain [19,58].…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…To date, neurological/psychiatric comorbidities represent a severe problem in PWE. As reported, comorbidities sometimes can be more harmful than seizures themselves [32,34]. The "face validity" of this animal model was also supported by the potential antiepileptogenic effect of ETH both in childhood absence epilepsy and this strain [19,58].…”
Section: Resultssupporting
confidence: 62%
“…It was proven that not only PWE have a greater risk to develop a neuropsychiatric disorder, but also patients with primary neuropsychiatric disorders are at greater risk of developing epilepsy. Accordingly, in some conditions, comorbidities and seizures can be generated independently from the same underlying network disease [32,34,35]. To support this linkage, it has also been demonstrated as several drugs acting on the catecholaminergic system, such as antidepressant drugs, could be potential candidate for the prevention and/or treatment of several types of epilepsy and its related neuropsychiatric comorbidities [36][37][38]; similarly different ASDs such as valproate and carbamazepine are often used in the clinical management of mood disorders [32,39,40].…”
Section: Wag/rij Rats and Neuropsychiatric Comorbiditiesmentioning
confidence: 99%
“…Furthermore, in our study we asked the patients whether they felt depressed or down/blue and did not use a more objective evaluation of depressive symptoms. 24 It is likely that many of the patients reporting feeling depressed in our survey do not have clinical depression, and this probably explains the high occurrence (nearly 60%) in our sample.…”
Section: Psychosocial Problemsmentioning
confidence: 78%
“…In a recent review, a number of studies suggested that depression is associated with an increased risk of epilepsy (55). The effectiveness of conventional antidepressant therapies is frequently examined in animals.…”
Section: Resultsmentioning
confidence: 99%